Poverty and Equivalence as Social Constructions - Lee Rainwater (Luxembourg Income Study (LIS), 1990)
This paper argues that a correct approach to the study of poverty must proceed from a sociologically grounded understanding of material and social well-being in modern societies. From reanalysis of Gallop poll data covering the period 1950-1968, this paper concludes that the elasticity of the poverty line is unitary.
Keywords: 330